Islamic Family Law Analysis of Mixed Marriage and Inheritance: The Legal Status of Children in Banten, Indonesia - Hikmatullah Hikmatullah; Ahmad Sanusi; Sayehu Sayehu; Itang Itang; Fandy Adven Lazavietamsi Itang (CV. Creative Tugu Pena, 2026)
This article aims to analyze the legal position of children in the context of mixed/interfaith marriage and interreligious inheritance disputes in Banten. The study employs normative legal research with statutory, case, and conceptual approaches, guided by fiqh al munakahat and fiqh al fara’id regarding spouses’ rights and obligations, lineage (nasab), and impediments to inheritance (mawani‘ al irth). Primary materials include (i) Supreme Court Circular Letter (SEMA) No. 2/2023, (ii) Constitutional Court decisions on marriage and child civil relations, (iii) a sample of Banten linked court products such as PN Tangerang determinations on interfaith marriage registration and Supreme Court Decision No. 434 K/AG/2025 connected to PA Tigaraksa and PTA Banten and (iv) Supreme Court jurisprudence on compulsory bequest (waṣiyyah wājibah) for non Muslim heirs. The findings show that: (1) judicial and administrative routes to register interfaith marriage have produced inconsistent outcomes and have been significantly restricted after SEMA No. 2/2023; (2) children’s civil documentation and paternal linkage remain legally possible through mechanisms of recognition and proof, but their position within Islamic inheritance may still be constrained by religious difference; and (3) Indonesian religious court jurisprudence has developed remedial mechanisms (waṣiyyah wājibah and, in certain cases, hibah wājibah) to protect excluded relatives without formally equating them to heirs under fara’id. The article’s novelty lies in integrating Banten specific judicial pathways (civil court determinations and religious court inheritance litigation) with an operational fiqh based analytic framework, producing a coherent protection model for children that remains faithful to both state law and Islamic legal principles.